Límites y Continuidad - Figueroa-Flores, Nuria (My University, 2017)
Se muestra tanto la teoría como ejemplos y práctica sobre límites de funciones y sus distintas formas indeterminadas.

It shows both theory and examples and practice about limits of functions and their different indeterminate forms.
Keywords: Teoría; Límites; Funciones; Matemáticas; Cálculo